Case report: Inhaled nitric oxide rescued a hypoxemia patient caused by dermatomyositis complicated with interstitial pneumonia - Wu, Xiaoyan; Zheng, Ruiqiang; Zhao, Zhanqi (Frontiers in Medicine, 2024)
Interstitial pneumonia is the most common and serious secondary lesion of dermatomyositis. In some cases, patients may develop severe acute pneumonia that can quickly progress to respiratory failure, resulting in high mortality rates. A 57-year-old woman with dermatomyositis and interstitial pulmonary fibrosis experienced severe hypoxemia due to pulmonary infection. Despite receiving various treatments after entering the intensive care unit (ICU), such as anti-infection therapy, lung recruitment, prone position ventilation, sedative and muscle relaxation, the patient’s oxygen saturation continued to decline. Electrical impedance tomography (EIT) monitoring revealed that prone position could not improve ventilation homogeneity. However, the patient’s ventilation/perfusion (V/Q) matching significantly improved 10 min after initiation of supine position ventilation combined with inhalation of nitric oxide (iNO). The patient’s PaO2/FiO2 (P/F) ratio increased from 86 mmHg to 150 mmHg at 30 min post-treatment. iNO treatment continued for 2 days. Then the patient’s condition improved and she was successfully weaned off the ventilator with rigorous monitoring and symptomatic care. The implementation of mechanical ventilation combined with iNO therapy rapidly improved V/Q matching and oxygenation in a patient with hypoxemia caused by dermatomyositis complicated with interstitial pneumonia. This approach successfully avoided the need for invasive extracorporeal membrane oxygenation (ECMO) support.